Nutritionally acquired immunodeficiency must be addressed with the same urgency as HIV to end tuberculosis - Madolyn R. Dauphinais; Kobto G. Koura; Prakash Babu Narasimhan; Saurabh Mehta; Julia L. Finkelstein; Scott K. Heysell; Pranay Sinha (BMC, 2024)
Abstract Tuberculosis (TB) is the leading infectious killer worldwide, with 10.6 million cases and 1.6 million deaths in 2021 alone. One in 5 incident TB cases were attributable to malnutrition, more than double the fraction attributed to HIV. Like HIV, malnutrition is a cause of secondary immunodeficiency and has even been dubbed nutritionally acquired immunodeficiency syndrome (N-AIDS). However, malnutrition remains the neglected cousin of HIV in global TB elimination efforts. Malnutrition increases the risk for TB progression, increases disease severity, and worsens TB treatment outcomes. Thus, it is both a TB determinant and comorbidity. In this perspective, we discuss decades of data to make the case that N-AIDS, just like HIV/AIDS, also deserves special consideration in the TB elimination discourse. Fortunately, malnutrition is a modifiable risk factor and there is now empirical evidence that addressing nutrition can help us curb the TB pandemic. Recognizing malnutrition as a key determinant and comorbidity is key to detecting and treating the missing millions while also preventing additional millions from suffering TB disease.